2021
DOI: 10.5187/jast.2021.e4
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid in Angus and Hanwoo (Korean native cattle) fat reduced the fatty acid synthase activity in rat adipose tissues

Abstract: This study aimed to determine the blood lipid profiles, fatty acid composition, and lipogenic enzyme activities in rat adipose tissues as affected by the Angus beef fat (ABF) and Hanwoo beef fat (HBF) containing high oleic acid (OA) content. We assigned 60 Sprague Dawley rats with a mean bodyweight of 249 ± 3.04 g to three groups (n = 20 each) to receive diets containing 7% coconut oil (CON), 7% ABF, or 7% HBF. The OA content was highest in the HBF (45.23%) followed by ABF (39.51%) and CON (6.10%). The final b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…39 Srebp-1c plays a central role in lipogenesis, enhancing the transcription of genes required for fatty acid syntheses, including fat acid synthase (Fas) and acetyl-CoA carboxylase 1 (Acc1). 40 Fas is a key enzyme controlling the rate of fatty acid synthesis, 41 while Acc1 is the rate-limiting enzyme in the biogenesis of long-chain fatty acids and regulation of fatty acid synthesis. 42 Our results showed that compared to the HFD mice, the Octa-treated mice showed significantly altered mRNA expressions of the above-mentioned genes, revealing the possibility of altered lipid metabolism through changes in the lipogenic genes caused by Octa in the HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…39 Srebp-1c plays a central role in lipogenesis, enhancing the transcription of genes required for fatty acid syntheses, including fat acid synthase (Fas) and acetyl-CoA carboxylase 1 (Acc1). 40 Fas is a key enzyme controlling the rate of fatty acid synthesis, 41 while Acc1 is the rate-limiting enzyme in the biogenesis of long-chain fatty acids and regulation of fatty acid synthesis. 42 Our results showed that compared to the HFD mice, the Octa-treated mice showed significantly altered mRNA expressions of the above-mentioned genes, revealing the possibility of altered lipid metabolism through changes in the lipogenic genes caused by Octa in the HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high total fatty acids and oleic acid contents are positively correlated with flavor [ 26 ], customer preference over imported beef [ 27 ], and favorable health characteristics for consumers [ 28 , 29 ]. Rats that eat Hanwoo beef fat show high feed intake but reduced lipogenic enzyme activities and increased high-density lipoprotein cholesterol, indicating a lower risk for cardiovascular disease compared to consuming Angus beef fat [ 30 ].…”
Section: Discussionmentioning
confidence: 99%